Unveiling the orchestration: mycobacterial small RNAs as key mediators in host-pathogen interactions - Garg, Rajni; Manhas, Ishali; Chaturvedi, Diksha (Frontiers in Microbiology, 2024)
Small RNA (sRNA) molecules, a class of non-coding RNAs, have emerged as pivotal players in the regulation of gene expression and cellular processes. Mycobacterium tuberculosis and other pathogenic mycobacteria produce diverse small RNA species that modulate bacterial physiology and pathogenesis. Recent advances in RNA sequencing have enabled identification of novel small RNAs and characterization of their regulatory functions. This review discusses the multifaceted roles of bacterial small RNAs, covering their biogenesis, classification, and functional diversity. Small RNAs (sRNAs) play pivotal roles in orchestrating diverse cellular processes, ranging from gene silencing to epigenetic modifications, across a broad spectrum of organisms. While traditionally associated with eukaryotic systems, recent research has unveiled their presence and significance within bacterial domains as well. Unlike their eukaryotic counterparts, which primarily function within the context of RNA interference (RNAi) pathways, bacterial sRNAs predominantly act through base-pairing interactions with target mRNAs, leading to post-transcriptional regulation. This fundamental distinction underscores the necessity of elucidating the unique roles and regulatory mechanisms of bacterial sRNAs in bacterial adaptation and survival. By doing these myriad functions, they regulate bacterial growth, metabolism, virulence, and drug resistance. In Mycobacterium tuberculosis, apart from having various roles in the bacillus itself, small RNA molecules have emerged as key regulators of gene expression and mediators of host-pathogen interactions.Understanding sRNA regulatory networks in mycobacteria can drive our understanding of significant role they play in regulating virulence and adaptation to the host environment.Detailed functional characterization of Mtb sRNAs at the host-pathogen interface is required to fully elucidate the complex sRNA-mediated gene regulatory networks deployed by Mtb, to manipulate the host. A deeper understanding of this aspect could pave the development of novel diagnostic and therapeutic strategies for tuberculosis.